An Analysis of Non-Verbal Communication in Students' Speaking Performance - Ronsani Thamrin, Nani; Darsih, Endang (KnE Social Sciences, 2023)
The aims of this study are to investigate the use of non-verbal communication in students’ speaking class and to describe the reasons of the use non-verbal communication in students’ speaking class at English Department, University of Kuningan. The participants of this study were three selected students of English education department who took public speaking subject in fourth semester. The study employed a qualitative research through a plying a case study design. To gain the data needed, two techniques were employed; observation and interview. The writer used observation field note to find out the types of non-verbal communication in students’ speech. Interview was conducted to answer the reasons toward the use of non-verbal communication in students’ speech. The data analysis showed that the most occur used non-verbal communication was gesture. Moreover, students’ prefer to use gesture and their eye contact to help them conveying message and as the complement to make their speech more interesting. It can be stated that non-verbal communication emphasize the students in delivering message to the audience while doing speech, in addition students were more confident when delivering their speech by using non-verbal communication. Keywords: Non-verbal; communication; public speaking